2002
DOI: 10.1074/jbc.m206488200
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 6 and Measles Virus Employ Distinct CD46 Domains for Receptor Function

Abstract: We employed a quantitative cell fusion assay to identify structural domains of CD46 required for its function as a receptor for human herpesvirus 6 (HHV-6). We examined the activities of recombinant variants of CD46, including different isoforms as well as engineered truncations and molecular chimeras with decay-accelerating factor, a related protein in the family of regulators of complement activation (RCA). We observed strong receptor activity for all four CD46 isoforms, which differ in the membrane-proximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 55 publications
4
44
0
Order By: Relevance
“…Using complementary co-immunoprecipitation approaches, we identified the gH glycoprotein as the CD46-binding component of HHV-6. Mapping studies demonstrated that the CD46 determinants critical for gH binding reside in SCR2 and SCR3, consistent with our previous study (5) indicating the importance of the same CD46 domains for HHV-6 fusion.…”
Section: Human Herpesvirus 6 (Hhv-6)supporting
confidence: 74%
See 3 more Smart Citations
“…Using complementary co-immunoprecipitation approaches, we identified the gH glycoprotein as the CD46-binding component of HHV-6. Mapping studies demonstrated that the CD46 determinants critical for gH binding reside in SCR2 and SCR3, consistent with our previous study (5) indicating the importance of the same CD46 domains for HHV-6 fusion.…”
Section: Human Herpesvirus 6 (Hhv-6)supporting
confidence: 74%
“…Flow cytometry analysis confirmed equivalent expression of all constructs (Ref. 5 and data not shown). As shown in Fig.…”
Section: Fig 2 Immunodepletion Of Gh Abrogates Cd46 Co-precipitatiomentioning
confidence: 90%
See 2 more Smart Citations
“…[38][39][40] HHV-6 is the only known herpesvirus that utilizes CD46 for infection and entry into the host cell. [41][42][43][44] Interestingly, a higher expression of CD46 is observed on the surface of untreated CB cells compared with G-CSF-mobilized hematopoietic progenitor cells used in HSCT, which may contribute to the increased prevalence of post-CBT HHV-6 reactivation. 10,45,46 However, several lines of evidence suggest that other cellular factors in addition to CD46 are crucial to the establishment of active HHV-6 infection in vivo.…”
Section: Discussionmentioning
confidence: 99%